Design of a Gravity Ropeway in Nepal: A Methodological Analysis for Appropriate Technologies - Elena Blanco-Romero; Carles Domènech-Mestres; Manuel Ayala-Chauvin (Machines)
This article describes the complete development of a design project for a context-integrated appropriate technology, a gravity ropeway for transporting agricultural products in remote areas of Nepal. The main purpose was to improve and optimize existing gravity ropeway designs, prioritizing simplicity, safety, and local manufacturability and maintenance. The design process followed a phased methodological approach used in machine design, which included stages of definition, conceptual design, materialization, and detailed design. The results of the ropeway installation demonstrate a reduction in the time and effort required by farmers to transport their products, consequently leading to a significant improvement in their quality of life. Despite the methodology followed, deficiencies were identified in the project execution procedure: lack of documentation and lack of explicit consideration of the local context in the design specifications, which could compromise the continuity and success of the project. This analysis highlights the need to adapt traditional design methodologies to appropriate technology projects. Specific procedures that address the characteristics of the local environment should be included to integrate the design into the context and accurately determine the needs of users in development projects.